Shear Wave Speed and Dispersion Measurements Using Crawling Wave Chirps. (October 2014) - Hah, Zaegyoo; Partin, Alexander; Parker, Kevin J.
This article demonstrates the measurement of shear wave speed and shear speed dispersion of biomaterials using a chirp signal that launches waves over a range of frequencies. A biomaterial is vibrated by two vibration sources that generate shear waves inside the medium, which is scanned by an ultrasound imaging system. Doppler processing of the acquired signal produces an image of the square of vibration amplitude that shows repetitive constructive and destructive interference patterns called "crawling waves." With a chirp vibration signal, successive Doppler frames are generated from different source frequencies. Collected frames generate a distinctive pattern which is used to calculate the shear speed and shear speed dispersion. A special reciprocal chirp is designed such that the equi-phase lines of a motion slice image are straight lines. Detailed analysis is provided to generate a closed-form solution for calculating the shear wave speed and the dispersion. Also several phantoms and an ex vivo human liver sample are scanned and the estimation results are presented.